Computed Tomography Features of Glenoid Osteophytes in Traumatic Anterior Shoulder Instability: Comparison Between Younger and Older Patients. Issue 5 (21st May 2019) - Hirose, Takehito; Nakagawa, Shigeto; Sato, Seira; Tachibana, Yuta; Mae, Tatsuo
Background: Osteoarthritis that develops after traumatic anterior shoulder instability is known as dislocation arthropathy, but its frequency and characteristics are still unclear. Purpose: To evaluate glenoid osteophytes in shoulders with traumatic anterior instability by using computed tomography (CT) and to elucidate the influence of instability on the progression of dislocation arthropathy in different age groups. Study Design: Cross-sectional study; Level of evidence, 3. Methods: This study involved 214 unoperated patients with unilateral instability who underwent CT of both shoulders. The patients were divided into 2 groups according to age at the time of CT: ≤30 years (younger group; n = 172) and ≥31 years (older group; n = 42). Patient demographics as well as the presence, size, and location of glenoid osteophytes were compared between the 2 groups and also between patients with and without osteophytes. Furthermore, patients with osteophytes in the older group were divided into 2 subgroups according to age at the time of the initial injury: as a teenager (early-onset subgroup; n = 9) or at ≥31 years (late-onset subgroup; n = 14), and the same assessments were conducted. Results: Osteophytes were significantly more frequent on the affected side of the older group compared with the younger group (71.4% vs 13.9%, respectively; P < .001). In the younger group, patients with osteophytes had more multiple-instability events ( P = .002) and a longer interval from injury to CT ( P < .001) than those without osteophytes. Although there was no difference in osteophyte size between the 2 groups, most osteophytes were located at the anteroinferior part of the glenoid in the younger group, while osteophytes were usually circumferential around the glenoid in the older group. A comparison between the early- and late-onset subgroups in older patients with osteophytes revealed that the osteophytes were more frequently located at the anteroinferior glenoid region in the early-onset subgroup. Conclusion: CT allowed a detailed evaluation of glenoid osteophytes, revealing that osteophytes were not uncommon in younger patients. Instability itself might influence the progression of osteoarthritic changes in younger patients, while aging seems to have a greater effect in older patients.